2006
DOI: 10.1002/jnr.20883
|View full text |Cite
|
Sign up to set email alerts
|

Strain difference in susceptibility to experimental autoimmune encephalomyelitis between Albino Oxford and Dark Agouti rats correlates with disparity in production of IL-17, but not nitric oxide

Abstract: Albino Oxford (AO) rats, unlike Dark Agouti (DA) rats are resistant to the induction of experimental autoimmune encephalomyelitis (EAE). The reason for the resistance could be some restraining mechanism preventing auto-aggressive cell activation at the level of draining lymph nodes (DLN) during the induction phase of the disease. Such a mechanism could be anti-proliferative action of nitric oxide (NO), which has already been shown of importance for the resistance of several rat strains to the induction of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
30
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 34 publications
(75 reference statements)
9
30
0
Order By: Relevance
“…More recently, a distinct population of Th17 IL-17-secreting cells has been increasingly gaining recognition for its importance in the pathology of CNS autoimmunity (Langrish et al, 2005). We have recently reported that both IL-17 and IFN-g gene expression and cytokine production by DLNC are much higher in EAE-prone DA rats than in EAE-resistant AO rats (Miljkovic et al, 2006), and here we show a clear dominance of CNS-infiltrating cells to DLNC in their ability to express both of these cytokines. It has previously been reported that cells infiltrating CNS at the peak of clinical EAE produced severalfold higher amounts of IFN-g compared with draining lymph node and spleen cells (Xiao et al, 1998;Hoffstetter et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…More recently, a distinct population of Th17 IL-17-secreting cells has been increasingly gaining recognition for its importance in the pathology of CNS autoimmunity (Langrish et al, 2005). We have recently reported that both IL-17 and IFN-g gene expression and cytokine production by DLNC are much higher in EAE-prone DA rats than in EAE-resistant AO rats (Miljkovic et al, 2006), and here we show a clear dominance of CNS-infiltrating cells to DLNC in their ability to express both of these cytokines. It has previously been reported that cells infiltrating CNS at the peak of clinical EAE produced severalfold higher amounts of IFN-g compared with draining lymph node and spleen cells (Xiao et al, 1998;Hoffstetter et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…The pronounced decrease in CNS T cells and the sustained T H 1 response following treatment with high doses of R(+)WIN55,212-2 led us to explore the T H 17 cell lineage since it has been linked to various autoimmune diseases including MS [59][60][61] . We found a dose-dependent decrease in T H 17-positive cells that mirrored EAE severity ( fig.…”
Section: Discussionmentioning
confidence: 99%
“…Both IL-17 and IFN-γ are continuously produced by DLNC and SCC in Dark Agouti rats immunized to develop EAE [16] . Furthermore, low production of IL-17 and IFN-γ in DLNC, as well as low production of the cytokines that induce IL-17 and IFN-γ generation (including IL-6, IL-12, and IL-23) in DLNC, have been associated with the resistance of Albino Oxford rats to EAE induction [17,18] . Regarding MS, it has been shown that IL-17 is elevated in immune cells within the CNS and at the periphery and that it contributes to the pathogenesis of the disease, eg through distortion of the blood-brain-barrier [19][20][21] .…”
Section: Wwwchinapharcom Blaževski J Et Almentioning
confidence: 99%